The Effect of Osteoblast Isolation Methods from Adult Rats on Osteoclastogenesis in Co-Cultures - Žižková, Radmila; Hedvičáková, Věra; Blahnová, Veronika Hefka; Sovková, Věra; Rampichová, Michala; Filová, Eva (International journal of molecular sciences, 2022)
Co-cultures of osteoblasts and osteoclasts are on the rise because they enable a more complex study. Diseases such as osteoporosis are related to a higher age. Thus, cell isolation from adult individuals is necessary. Osteoblasts can be isolated from the rat femur by three methods: explant culture, explant culture with enzymatic pre-treatment, or enzymatic treatment. The isolation methods yield different populations of osteoblasts which, in a co-culture with peripheral blood mononuclear cells, might result in differences in osteoclastogenesis. Therefore, we examined the differences in osteogenic markers, cell proliferation, and the metabolic activity of isolated osteoblast-like cells in a growth and differentiation medium. We then evaluated the effect of the isolated populations of osteoblast-like cells on osteoclastogenesis in a subsequent co-culture by evaluating osteoclast markers, counting formed osteoclast-like cells, and analyzing their area and number of nuclei. Co-cultures were performed in the presence or absence of osteoclastogenic growth factors, M-CSF and RANKL. It was discovered that enzymatic isolation is not feasible in adult rats, but explant culture and explant culture with enzymatic pre-treatment were both successful. Explant culture with enzymatic pre-treatment yielded cells with a higher proliferation than explant culture in a growth medium. The differentiation medium reduced differences in proliferation during the culture. Some differences in metabolic activity and ALP activity were also found between the osteoblast-like cells isolated by explant culture or by explant culture with enzymatic pre-treatment, but only on some days of cultivation. According to microscopy, the presence of exogenous growth factors supporting osteoclastogenesis in co-cultures was necessary for the formation of osteoclast-like cells. In this case, the formation of a higher number of osteoclast-like cells with a larger area was observed in the co-culture with osteoblast-like cells isolated by explant culture compared to the explant culture with enzymatic pre-treatment. Apart from this observation, no differences in osteoclast markers were noted between the co-cultures with osteoblast-like cells isolated by explant culture and the explant culture with enzymatic pre-treatment. The TRAP and CA II activity was higher in the co-cultures with exogenous growth than that in the co-cultures without exogenous growth factors on day 7, but the opposite was true on day 14. To conclude, explant culture and explant culture with enzymatic pre-treatment are both suitable methods to yield osteoblast-like cells from adult rats capable of promoting osteoclastogenesis in a direct co-culture with peripheral blood mononuclear cells. Explant culture with enzymatic pre-treatment yielded cells with a higher proliferation. The explant culture yielded osteoblast-like cells which induced the formation of a higher number of osteoclast-like cells with a larger area compared to the explant culture with enzymatic pre-treatment when cultured with exogenous M-CSF and RANKL.
Keywords: Osteoclasts; Macrophage Colony-Stimulating Factor; Cells, Cultured; ligand RANK; leukocyty mononukleární; Osteogenesis; RANK Ligand; krysa rodu Rattus; Coculture Techniques; osteoklasty; kultivované buňky; osteogeneze; buněčná diferenciace; faktor stimulující kolonie makrofágů; zvířata; osteoblasty; kokultivační techniky; Rats; adult rat; Animals; Osteoblasts; co-culture; Leukocytes, Mononuclear; osteoblast-like cell; osteoclast-like cell; Cell Differentiation; mature bone